Combined active and passive microwave sensing of ocean surface wind vector from TRMM - Kasparis, Takis; Soisuvarn, Seubson; Jones, Wilma L. (My University, 2003)
This paper presents a new ocean wind vector measurement technique that uses the combined passive and active microwave measurements respectively from the Tropical Rainfall Measuring Mission (TRMM) Microwave Imager (TMI) and the Precipitation Radar (PR). The wind speed is inferred by TMI over a wide swath that includes the narrower PR swath. The PR scans cross-track ± 18°; and near the swath edges, where the radar backscatter responds to both the magnitude and direction of the surface wind, we use the microwave radiometer estimate of wind speed and the measured sigma-0 at incidence angles greater than 15 degrees to derive wind direction. Because the PR provides only a single azimuth look, multiple possible wind direction solutions exist. The ability to select the proper (single) direction is beyond the scope of this paper; but comparisons are presented between the "closest" retrieved TRMM wind vectors and near-simultaneous wind vectors measured by the QuikSCAT satellite scatterometer to demonstrate the potential for measuring ocean surface vector winds.
Keywords: Image converters; Radar; Radiometers; Microwaves; Winds